Cinc edicions del Venturós Pelegrí a la Bibliothèque Mazarine de París. - CLIMENT, JOAN MAHIQUES (Scripta, 2015)
The Ms. 4504 of the Bibliothèque Mazarine in Paris contains, on the one hand, five printed copies of the «Peregrinadó del Venturós Pelegrí» ab les «Cobles de la Mort» and, on the other hand, a partial hand-written copy of the Venturós Pelegrí with an incomplete French translation by Josep Tastu (1787-1849), who compiled all the materials of this volume. Apart from presenting the general content of the ms. 4504, we describe in detail the five editions with particular emphasis on the oldest one, probably dating from the mid-sixteenth century or shortly thereafter. This printed book, now acephalous and apodous, in which the lines go all the way across the page, still preserves three woodcuts. As the earliest witness we know of the Venturós Pelegrí, this printed copy provides some evidences to understand the dissemination of this work during the sixteenth and seventeenth centuries.